The Interface of Psychiatry and Religion: A Program for Career Training in Psychiatry - Westendorp, Floyd (Journal of psychology and theology, 1982)
The Church has a long history of being involved in psychiatry, however, few training programs have attempted to address the issues regarding the interface of psychiatry and religion. This article describes the development of a new psychiatric residency training program, its curriculum, the problems encountered, and a challenge for the future.